Cai Yuanpei’s Vision of Aesthetic Education and His Legacy in Modern China - LUO, Ning (Nordic Journal of Comparative and International Education, 2021)
Cai Yuanpei is widely understood to have been a traditionally educated Chinese scholar who then turned his attention to Western philosophy. He is known to have played a central role in the development of Republican educational philosophies and institutions, with a legacy that continues to inform education in China. Studies tend to interpret Cai Yuanpei’s approach to aesthetic education in light of his educational experience in Germany, regarding him as a Kantian scholar. However, the Confucian roots of his aesthetic education seldom draw scholarly attention. To fill the gap, this article examines Cai’s vision of aesthetic education based on both his academic background in the East and his knowledge of Western philosophy and maps out his influence on and legacy in aesthetic education in China. It argues that Cai’s vision of aesthetic education has influenced modern Chinese education in three main ways: by bridging the gap between moral education and aesthetic education to nurture citizenship, by encouraging aesthetic education for whole-person development, and by adopting an interdisciplinary approach to school aesthetic education. The article concludes by reflecting on the enduring value of Cai’s vision of aesthetic education to modern Chinese education.